2020
DOI: 10.1007/978-3-030-49815-3_4
|View full text |Cite
|
Sign up to set email alerts
|

A Sleep Monitoring Method with EEG Signals

Abstract: Diagnosis of sleep disorders is still a challenging issue for a large number of nerve diseases. In this sense, EEG is a powerful tool due to its non-invasive and real-time catacteristics. This modality is being more and more used for diagnosis such as for epilepsy. It is also becoming widely used for many redictive, Preventive and Personalized Medicine (PPPM) applications. To understand sleep disorders, we propose a method to classify EEG signals in order to detect abnormal behaviours that could reflect a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…Based on multiple experimental settings, the best configuration was obtained with a dropout of 0.85 for the convolutional part and 0.5 before the final classification. The obtained accuracy rate is higher that the one reported in [10] (93%) where the authors showed that their approach outperforms other state-of-the-art methods.…”
Section: A Validation With a Frame Leave-p-out Strategycontrasting
confidence: 63%
See 1 more Smart Citation
“…Based on multiple experimental settings, the best configuration was obtained with a dropout of 0.85 for the convolutional part and 0.5 before the final classification. The obtained accuracy rate is higher that the one reported in [10] (93%) where the authors showed that their approach outperforms other state-of-the-art methods.…”
Section: A Validation With a Frame Leave-p-out Strategycontrasting
confidence: 63%
“…Due to the difficulty to define a relevant analytical model for the drowsy state, machine learning tools have been investigated in the literature. In this sense, support vector machines (SVM) have been proposed to analyse EEG signals [9,10]. With the emergence of deep CNN, many studies have been conducted by proposing different architectures for EEG analysis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Over this decade, many EEG-based research works related to machine learning (ML) [ 27 , 28 , 29 , 30 ] have been suggested in medical diagnosis, in particular for classification-based drowsiness detection tasks. Nevertheless, some limitations appear in ML applications such as the need for a massive dataset to train, limitation predictions in return, the need of an intermediary step for feature representation and drawing conclusions to detect anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Drowsiness is a major factor in high rates of vehicle accidents. The use of non-invasive biomedical signals for drowsiness detection is an important and open issue that has recently received a considerable interest [54]- [58].…”
Section: Real-world Polysomnographic Data Analysismentioning
confidence: 99%
“…The obtained classification and detection performance are quantified using 2-class accuracies as in [58], and F-measure and area-under-curve (AUC) for the receiver operational characteristics (ROCs), as reported in Table III. To further illustrate the detection performance, the ROCs are displayed in Fig.…”
Section: B Drowsiness Detectionmentioning
confidence: 99%